Opportunities for a Just Transition to environmental sustainability and COVID-19 recovery in the textile and garment sector in Asia - Samantha Sharpe; Katarina Veem; Karina Kallio; M. Cristina Martinez-Fernandez (International Labour Organization (ILO), 2022)
The impact of COVID-19 on the textile and garment sector in Asian countries has been and continues to be immense, and may last for a very long time. While countries in the West are emerging from the pandemic with some optimism that life will soon return to pre-pandemic levels, new COVID-19 outbreaks in Asia are pushed back hopes for a recovery in 2021 and the health and mental effects in communities are challenging pre-pandemic achievements related to the United Nations' Sustainable Development Goals. This paper examines the impact of the COVID-19 pandemic on the textile and garment sector, specifically the employment and enterprise impacts, and contextualizes these within the wider development impacts of the sector - social, economic and environmental; both positive and negative - to ask the question: how sustainable is the sector? A Just Transition for the garment industry in Asia is critical as the sector seeks to recover from the impacts of COVID-19. This recovery comes also in a critical decade of action for achieving the Paris Agreement and the Sustainable Development Goals, both of which will also alter the future of work in the sector. The pandemic has highlighted that vulnerability is not equally shared across the supply chain, so too for carbon emissions, with emissions concentrating in specific production activities, and these activities geographically concentrated in certain hot-spots - areas that are both highly reliant on the textile and garment sector, but also highly vulnerable to supply chain disruptions and other impacts on the sector. This creates a strong spatial dimension to the need for planning for a Just Transition in the industry; hot spots in local areas can be turned into opportunities for accelerated community action to "build back better".
Keywords: 330; green jobs; sustainable development; clothing and textile industries; partnerships